4 - Mothers’ Constructions of their Roles in the Literacy Education of their Children - Anyikwa, Ngozi; Obidike, Ngozi (Africa Development, 2021)
This paper presents findings from a study that examined how mothers from a middle-income neighbourhood conceptualized their roles in their children’s literacy education. Based on interviews and observations focussed on ten mothers involvement in their children’s literacy education, a framework that expounds typical characterizations of parent involvement was developed which supports practices that are both traditionally visible and invisible to the school and highlights how parents act as ‘intellectual resources’ in their children’s literacy education. The findings show that traditional understandings of parental involvement may overlook ways that middle-income parents deliberately involve themselves in their children’s education. Challenges that these parents face in relation to their involvement in their children’s literacy education were identified.